The Teutonic Order in Italy, 1190-1525 - Toomaspoeg, Kristjan, author.
1 online resource.
Keywords: Between 1190 and 1525, the Teutonic Order (the third major military religious order after the Temple and the Hospital) maintained extensive possessions in Italy. This volume examines the history of the Order's Italian branch, arguing that it served as an intermediary between East and West, as well as North and South. It reflects on the reasons for the Teutonic Order's success and the persistence of its settlement, particularly its ability to adapt to various and changing political and economic contexts, and its talent in garnering the support of the local population. Not only focusing on political, diplomatic, economic and religious history but also considering the history of art and architecture, spirituality, prosopography and everyday life, this book portrays the Teutonic Order in Italy as an example of medieval coexistence, collaboration and crossing borders. This book will a useful study for scholars interested in Medieval Italy, cross-cultural history and the military religious orders of the medieval period.